Therapeutic Efficacy of Potassium Citrate for Treating Less Than 10-Millimeter Renal Stones - Fateme Guitynavard (Urology Research Center, 2021)
Introduction: To assess the therapeutic efficacy of potassium citrate in the nonsurgical management of renal stones we run this research. The prophylactic effects of Potassium Citrate over renal stone formation have been established but there is still a gap for its therapeutic effect. Methods: A written informed consent was given to the patients who fulfilled the inclusion criteria and were interested in participation. Eventually 56 patients (Mean age= 43.7 ± 10.8) from June 2018 to December 2018 with a total of 86 renal stones enrolled in the study and treated with potassium citrate (10 mEq Alithoral, Nooria Darman Pasargad, tablets, three times a day). Moreover, the patients were recommended to reduce sodium intake as well as oxalate-rich foods, have at least 2 liters of water per day and normalize calcium intake. Finally, they were assessed 8 weeks after the treatment initiation, while in those whose stones were remained, the assessments repeated for another 8-week. Results: Based on our findings, 42 and 25 stones were completely dissolved at the first and second visit, respectively. Compared to the baseline parameters, the mean size of stones in the largest diameter decreased significantly from 5.13 to 1.96 mm and 5.13 to 0.79 mm (p-value<0.001) at the first and second visit, respectively. Conclusion: Potassium citrate plays a crucial role in pulverizing and also reduction of the dimensions of the renal stone. Therefore, apart from the prevention of renal stones recurrence, potassium citrate can be used in favor of treating renal stones.